85.5k views
5 votes
In the equation below assume U and A are know.

Rearrange the equation so that you would solve for R in terms of the Greek letter sigma)
U = R − 1 2 A σ 2
A. R = U − 1 2 A σ 2
B. R = 1 2 A σ 2 U
C. R = U 1 2 A σ 2

1 Answer

3 votes

Answer:


R = U + {1}{2}A\sigma^2

Step-by-step explanation:

Given


U = R - (1)/(2)A\sigma^2

Required

Solve for R

We have:


U = R - {1}{2}A\sigma^2

Add
{1}{2}A\sigma^2 to both sides


U + {1}{2}A\sigma^2 = R - {1}{2}A\sigma^2 + {1}{2}A\sigma^2

Evaluate like terms


U + {1}{2}A\sigma^2 = R

Hence:


R = U + {1}{2}A\sigma^2

User Sebastian Zartner
by
4.5k points